PRESIDENTIAL CONTROL OVER AGENCIES: WHEN DOES ENOUGH BECOME TOO MUCH? (Utah Environmental Law Review; Vol 29 No 2 (2009))
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} It is easy to see the problems too much power in the hands of the Executive Branch caused in the days of Guantanamo, wiretaps, Massachusetts v. EPA , and destroyed torture videos. Without checks and balances in place, the power of any branch will expand until stopped. This is the very problem the first European immigrants to these shores were trying to escape, and the reason our governmental structure is tripartite. This Note will explore the circumstances that coincidentally aligned to give the Executive too much power over administrative agencies. Finally, it will determine whether the situation will eventually right itself, or if not, and whether anything can be done to redress the power imbalance.